A new quantum dot-platinum conjugate for self-assembled nanoconjugates by coordination bonding mediated recognition - Lee, Jiyeon; Kim, Heeyeon; Sim, Taebo; Song, Rita (ROYAL SOC CHEMISTRY, 2013)
A new binding strategy of linking quantum dots (QDs) to magnetic nanoparticles (MNPs) using DNA interaction with metal coordination bonding was developed. Platinum was selected for binding QDs to DNA. This novel self-assembled nanoconjugate would be a new probe for diagnosing a specific disease more accurately with its double modalities, fluorescence and magnetic property.
Keywords: NUCLEIC-ACIDS; DNA; DELIVERY; PROBES; NANOPARTICLES; FLUORESCENCE; PROTEASE; OXIDE